A composite high barrier film based on POE material and its application
By adopting a three-layer composite high-barrier film structure, combined with the melt index control of POE and PVDC or EVOH materials and the use of crosslinking agents, the problems of easy adhesion, poor thermal performance and high cost of existing solar panel packaging films are solved, and efficient light transmission and water blocking effects are achieved, reducing the cost of the sealing film.
Patent Information
- Application Number
- CN202211688282.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-12-27
AI Technical Summary
The existing solar panel packaging film is easy to stick to mold, has poor thermal performance, low surface hardness and high cost, and is difficult to process POE materials, and the precipitation of polar additive solvents leads to smooth surface displacement.
A three-layer composite high-barrier film structure is adopted, including a POE film layer, a PVDC or EVOH film layer and a POE film layer. By controlling the melt index of POE and polylactic acid, a peroxide crosslinker and a silane coupling agent are added to optimize the light transmittance and adhesion properties of the adhesive film.
The light transmittance of the adhesive film and the efficiency of the use of solar panels are improved, the adhesion performance and water-blocking effect of the film layer are enhanced, the cost of the sealant film is reduced, and the thermal stability and photo-aging resistance of the adhesive film are improved.
Smart Images

Figure BDA0004020149960000091 
Figure BDA0004020149960000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells and the field of H01L51 / 52, and more specifically to a composite high-barrier film based on POE material and application thereof. Background Art
[0002] The utilization of solar energy is mainly to convert it into electrical energy through solar panels, and then convert it into other uses. Since the working environment of solar cell modules is mainly outdoors, and solar cells cannot be directly exposed to natural conditions such as sunlight and rain, it is necessary to seal them. At present, the solar cells are mainly encapsulated by a highly transparent, UV-resistant, aging-resistant, adhesive layer with good adhesion and elasticity, and bonded together with the upper protective material (front plate) and the lower protective material (back plate) to form a solar panel. Traditional EVA materials and POE materials have low water vapor permeability and high volume resistivity, which ensures the operation of the components in high temperature and high humidity environments.
[0003] CN103146315A discloses a high volume resistivity EVA film and its preparation process, wherein the composition of the EVA film is: 82% to 94% EVA resin, 5% to 15% polyolefin elastomer (POE), and additives. The high volume resistivity EVA film in the patent reduces the VA content, reduces the generation of conductive ions, and can improve the resistivity. However, the film obtained with EVA material as the substrate is easy to stick to the mold, is easily decomposed by heat, has poor thermal properties, has low surface hardness, and is easy to scratch.
[0004] CN113004815A discloses a solar cell encapsulation film and its preparation method, wherein the film comprises three layers, namely, EVA layer, POE layer and EVAPOE blended layer, which can simultaneously improve volume resistivity and water vapor barrier performance compared to ordinary EVA film, and has excellent insulation performance and anti-attenuation performance in a hot and humid environment. However, POE has high cost and low polarity. During the film processing, polar additive solvent precipitates to the film surface, causing the surface to be smooth and easy to shift; the processing difficulty is relatively large, and the film lip is easy to hang material. Summary of the invention
[0005] In view of the above problems, the present invention discloses a composite high-barrier film based on POE material, wherein the composite high-barrier film comprises three layers, namely: a POE film layer, a PVDC film layer or an EVOH film layer, and a POE film layer.
[0006] In one embodiment, the raw materials for preparing the POE film layer include, by mass: 60-85 parts of POE (ethylene-octene copolymer), 1-1.8 parts of toughening agent polylactic acid, 0.4-0.9 parts of peroxide crosslinking agent, and 0.15-0.58 parts of silane coupling agent.
[0007] Preferably, the raw materials for preparing the POE film layer include, by mass: 77 parts of POE (ethylene-octene copolymer), 1.2 parts of toughening agent polylactic acid, 0.56 parts of peroxide crosslinking agent, and 0.34 parts of silane coupling agent.
[0008] In one embodiment, the POE melt index is less than 0.9 g / 10 min.
[0009] Preferably, the POE has a melt index of less than 0.7 g / 10 min, for example, POE purchased from SABIC of Korea, C0560D, has a melt index of 0.5 g / 10 min.
[0010] The melt index is measured under the conditions of 190° C. and 2.16 kg.
[0011] In one embodiment, the melt index of the toughening agent polylactic acid is greater than 15 g / 10 min.
[0012] Preferably, the toughening agent polylactic acid has a melt index greater than 16 g / 10 min, such as the Shanghai Tongjieliang Biomaterials Co., Ltd. model IM9005, with a melt index of 20-30 g / 10 min.
[0013] The melt index is measured under the conditions of 210° C. and 2.16 kg.
[0014] POE is composed of carbon and hydrogen atoms. There are no active groups on the surface of the material. It is a typical non-polar substance. However, polar additives are often added during the processing of adhesive films. They contain electron-rich atoms such as nitrogen and oxygen, which have a large polarity, so that there is only a small intermolecular force between the POE substrate and the adhesive, causing the problem of smooth surface and easy displacement. Then, after a series of subsequent studies, the applicant unexpectedly discovered that it is only necessary to control the POE melt index to be less than 0.9g / 10min and the toughening agent polylactic acid melt index to be greater than 15g / 10min to solve the above problems. The applicant believes that the possible reason is that when the melt index between POE and polylactic acid is large, the steric hindrance between the molecules is large, so that the polylactic acid molecules are evenly dispersed between the POE molecules, avoiding the migration of small molecular weight substances to the surface of the film, and gathering on the surface of the material to form a weak boundary layer, making it difficult for the bonding effect to take effect, causing the problem of smooth surface and easy displacement.
[0015] In one embodiment, the peroxide crosslinking agent is selected from one or more of tert-butyl perbenzoate (TBPB), tert-butyl peroxide 3,5,5-trimethylhexanoate (TBPIN), dicumyl peroxide (DCP), and 1,4-di-tert-butyl peroxyisopropylbenzene.
[0016] Preferably, the peroxide crosslinking agent is tert-butyl peroxide 3,5,5-trimethylhexanoate.
[0017] In one embodiment, the silane coupling agent is selected from 3-aminopropyl triethoxysilane, γ-(2,3-epoxypropyloxy)propyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl methyl dimethoxysilane, γ-mercaptopropyl trimethoxysilane, hexamethyldisilazane, phenylmethyltrimethylpolysiloxane, 1,3-bis(3-methacryloxypropyl)tetramethyldisiloxane, 1,3-dibenzyltetramethyldisiloxane, polydimethylsiloxane, vinyltrimethoxysilane, acryltrimethoxysilane and one or more thereof.
[0018] Preferably, the silane coupling agent is a compound of polydimethylsiloxane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of 1:(7-12).
[0019] The POE used in the present invention has a melt index of less than 0.9 g / 10 min and a large molecular weight, which makes it difficult for the molecular chain to move and diffuse, especially the molecular arrangement on the surface of POE is very tight and the porosity is low, which is beneficial for water blocking, but the light transmittance is also reduced, and the solar energy efficiency is reduced. Then, after a series of subsequent studies, the applicant unexpectedly found that the addition of a peroxide cross-linking agent and a small amount of a silane coupling agent can improve the light transmittance of the film. The applicant believes that the possible reason is that the peroxide cross-linking agent forms peroxide free radicals, which can promote the generation of POE free radicals. Under the action of the cross-linking agent, the chain length rapidly increases and crystallizes or forms a network structure. The formation of the network structure is intentional to the POE film, and the crystallization of the molecular chain will form crystals in the film, making it impossible for light to penetrate, affecting the light transmission performance. The crystallization of the molecular weight is in a competitive relationship with the formation of the network structure. Adding a small amount of a silane coupling agent can form a silicon-oxygen bond between molecules, making the network structure in the cross-linking process the main reaction, enriching the network structure of the system while improving the porosity of the system, and improving the light transmittance while having excellent water blocking performance, so that the use efficiency of the solar panel is improved.
[0020] In one embodiment, the raw materials for preparing the PVDC film layer are, by weight: 75-95 parts of vinylidene chloride monomer, 20-24 parts of modifier, 1-2 parts of emulsifier, 0.2-0.3 parts of initiator, and 50-60 parts of deionized water.
[0021] Preferably, the raw materials for preparing the PVDC film layer are, by weight: 85 parts of vinylidene chloride monomer, 21 parts of modifier, 1.8 parts of emulsifier, 0.2 parts of initiator, and 52 parts of deionized water.
[0022] The mass percentage standard of the PVDC film layer is different from the mass percentage standard of the POE film layer.
[0023] In one embodiment, the modifier is selected from any one of glycidyl acrylate and allyl glycidyl ether.
[0024] Preferably, the modifier is glycidyl acrylate.
[0025] In one embodiment, the emulsifier is selected from one or more of sodium dodecyl sulfate, sodium pentadecyl sulfate, and sodium octadecyl sulfate.
[0026] Preferably, the emulsifier is sodium lauryl sulfate.
[0027] In one embodiment, the initiator is selected from one or more of dimethyl azobisisobutyrate, potassium persulfate, benzoyl peroxide, lauroyl peroxide, sodium persulfate, ammonium persulfate, azobisisobutyronitrile, and azobisisoheptylonitrile.
[0028] Preferably, the initiator is a compound of dimethyl azobisisobutyrate and potassium persulfate in a mass ratio of 1:(8-15).
[0029] Further preferably, the mass ratio of dimethyl azobisisobutyrate to potassium persulfate is 1:12.
[0030] In order to ensure that the PVDC layer has excellent water vapor barrier properties, the PVDC particle size distribution must be controlled so that the PVDC particle size distribution is narrow, and the average molecular weight of the polymer is controlled at 500-1000 to avoid reduced flexibility after film formation. After a series of subsequent studies, the applicant unexpectedly found that by controlling the initiator to be a compound of dimethyl azobisisobutyrate and potassium persulfate, with a mass ratio of 1: (8-10), it can be ensured that the average particle size of the generated PVDC latex is 1.0-1.3 μm, the average molecular weight of the polymer is controlled at 500-1000, and it has good water vapor barrier properties and flexibility. The applicant believes that the possible reason is that inorganic peroxides are water-soluble initiators with a moderate initiation rate, which can make the average particle size of the PVDC latex 0.8-1.5 μm and the average molecular weight of the polymer controlled at 500-2000, and adding a small amount of dimethyl azobisisobutyrate can further balance the reaction process, thereby achieving a narrower particle size distribution of the obtained PVDC.
[0031] In one embodiment, the EVOH melt index is greater than 3.5 g / 10 min.
[0032] Preferably, the EVOH has a melt index greater than 4 g / 10 min. For example, the EVOH purchased from Kuraray of Japan has a brand name of F104B and a melt index of 4.4 g / 10 min.
[0033] The melt indexes are all measured at 210° C. and 2.16 kg.
[0034] Those skilled in the art know that after three to four years of continuous use, traditional EVA encapsulation films will have serious aging problems, and may even crack and debond, which will reduce the sealing performance of solar cells and seriously affect the battery life. POE materials have low water vapor permeability and high volume resistivity, which ensures that the components can operate in high temperature and high humidity environments. However, POE films are expensive, and polar additive solvents are precipitated onto the film surface during film processing, resulting in a smooth surface that is easy to shift. Therefore, the applicant envisions the use of a three-layer composite film technology with a POE film as the outer layer and a PVDC film or EVOH film as the middle layer. However, how to ensure good bonding performance of the three-layer film has become the key to the technology of the present invention. The applicant has found in a large number of studies that controlling the EVOH melt index to be greater than 3.5g / 10min can improve the bonding performance between POE film and PVDC film or between POE and EVOH. The inventor believes that the possible reason is that the outer layer POE film has a lower melt index, while the PVDC film and EVOH film have high melt indexes. During the three-layer co-extrusion process, EVOH and PVDC with high melt indexes can fuse with the outer layer faster, thereby ensuring good bonding performance of the three-layer film. In addition, the original properties of the three-layer film will not change. The resulting composite film has good toughness, low water vapor permeability, good water barrier effect, good light transmittance, high barrier properties, and resistance to light aging. In addition, the cost of the sealing film is greatly reduced.
[0035] Another aspect of the present invention discloses a method for preparing the composite high-barrier membrane, which comprises co-extruding three layers of mixed materials, cooling and shaping the same.
[0036] Preferably, the PVDC film preparation method comprises: after the materials are evenly mixed, ethylenediaminetetraacetic acid is used to adjust the pH of the emulsion to 6-6.8, the temperature is raised to 48-55° C. under N2 conditions, stirred for 9-12 hours, and cooled to discharge the materials.
[0037] Further preferably, the method for preparing the PVDC film layer is as follows: after the materials are evenly mixed, ethylenediaminetetraacetic acid is used to adjust the pH of the emulsion to 6.5, the temperature is raised to 50° C. under N2 conditions, stirred for 10 hours, and cooled to discharge the material.
[0038] The composite high-barrier diaphragm of the present invention is applied to N-type batteries and HJT batteries.
[0039] Beneficial effects:
[0040] 1. The present invention avoids the problems of easy displacement due to smooth surface and easy hanging of film lips by making the POE melt index less than 0.9g / 10min and the toughening agent polylactic acid melt index greater than 15g / 10min.
[0041] 2. The present invention adds a peroxide cross-linking agent and a small amount of silane coupling agent to improve the light transmittance of the film and improve the solar energy efficiency.
[0042] 3. The present invention ensures that the PVDC layer has excellent water vapor barrier properties by controlling the initiator to be a compound of dimethyl azobisisobutyrate and potassium persulfate in a mass ratio of 1:(8-10).
[0043] 4. The composite high barrier film obtained by the present invention has good bonding performance between film layers, and the obtained composite film has good toughness, low water vapor permeability, good water barrier effect, good light transmittance, high barrier properties, resistance to light aging, and greatly reduces the cost of the sealing film.
[0044] 5. The composite high-barrier diaphragm obtained by the present invention is applied to N-type batteries and HJT batteries. DETAILED DESCRIPTION
[0045] Example 1
[0046] This embodiment 1 discloses a composite high-barrier film based on POE material, and the composite high-barrier film includes three layers, namely: a POE film layer, a PVDC film layer, and a POE film layer.
[0047] The raw materials for preparing the POE film layer are as follows, by mass: 60 parts of POE, 1 part of toughening agent polylactic acid, 0.4 parts of peroxide crosslinking agent, and 0.15 parts of silane coupling agent.
[0048] The POE was purchased from SABIC of Korea with the brand number C0560D.
[0049] The toughening agent polylactic acid was purchased from Shanghai Tongjieliang Biomaterials Co., Ltd., model number IM9005.
[0050] The peroxide crosslinking agent is tert-butyl peroxide 3,5,5-trimethylhexanoate.
[0051] The silane coupling agent is a compound of polydimethylsiloxane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane, with a mass ratio of 1:7.
[0052] The raw materials for preparing the PVDC film layer are, by weight: 95 parts of vinylidene chloride monomer, 24 parts of modifier, 2 parts of emulsifier, 0.3 parts of initiator, and 60 parts of deionized water.
[0053] The mass percentage standard of the PVDC film layer is different from the mass percentage standard of the POE film layer.
[0054] The modifier is glycidyl acrylate.
[0055] The emulsifier is sodium lauryl sulfate.
[0056] The initiator is a compound of dimethyl azobisisobutyrate and potassium persulfate, with a mass ratio of 1:8.
[0057] The PVDC film preparation method comprises the following steps: after the materials are uniformly mixed, ethylenediaminetetraacetic acid is used to adjust the pH value of the emulsion to 6.5, the temperature is raised to 50° C. under N2 conditions, the mixture is stirred for 10 hours, and the mixture is cooled and discharged.
[0058] On the other hand, this embodiment 1 discloses a method for preparing the composite high-barrier membrane, which is obtained by co-extruding the three-layer mixed material, cooling and shaping.
[0059] Example 2
[0060] This embodiment 2 discloses a composite high-barrier film based on POE material, and the composite high-barrier film includes three layers, namely: a POE film layer, a PVDC film layer, and a POE film layer.
[0061] The raw materials for preparing the POE film layer are as follows, by weight: 85 parts of POE, 1.8 parts of toughening agent polylactic acid, 0.9 parts of peroxide crosslinking agent, and 0.58 parts of silane coupling agent.
[0062] The POE was purchased from SABIC of Korea with the brand number C0560D.
[0063] The toughening agent polylactic acid was purchased from Shanghai Tongjieliang Biomaterials Co., Ltd., model number IM9005.
[0064] The peroxide crosslinking agent is tert-butyl peroxide 3,5,5-trimethylhexanoate.
[0065] The silane coupling agent is a compound of polydimethylsiloxane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane, with a mass ratio of 1:12.
[0066] The raw materials for preparing the PVDC film layer are, by weight: 75 parts of vinylidene chloride monomer, 20 parts of modifier, 1 part of emulsifier, 0.2 parts of initiator, and 50 parts of deionized water.
[0067] The mass percentage standard of the PVDC film layer is different from the mass percentage standard of the POE film layer.
[0068] The modifier is glycidyl acrylate.
[0069] The emulsifier is sodium lauryl sulfate.
[0070] The initiator is a compound of dimethyl azobisisobutyrate and potassium persulfate, with a mass ratio of 1:15.
[0071] The PVDC film preparation method comprises the following steps: after the materials are uniformly mixed, ethylenediaminetetraacetic acid is used to adjust the pH value of the emulsion to 6.5, the temperature is raised to 50° C. under N2 conditions, the mixture is stirred for 10 hours, and the mixture is cooled and discharged.
[0072] On the other hand, this embodiment 2 discloses a method for preparing the composite high-barrier membrane, which is obtained by co-extruding the three-layer mixed material, cooling and shaping.
[0073] Example 3
[0074] This embodiment 3 discloses a composite high-barrier film based on POE material, and the composite high-barrier film includes three layers, namely: a POE film layer, a PVDC film layer, and a POE film layer.
[0075] The raw materials for preparing the POE film layer are as follows, by weight: 77 parts of POE, 1.2 parts of toughening agent polylactic acid, 0.56 parts of peroxide crosslinking agent, and 0.34 parts of silane coupling agent.
[0076] The POE was purchased from SABIC of Korea with the brand number C0560D.
[0077] The toughening agent polylactic acid was purchased from Shanghai Tongjieliang Biomaterials Co., Ltd., model number IM9005.
[0078] The peroxide crosslinking agent is tert-butyl peroxide 3,5,5-trimethylhexanoate.
[0079] The silane coupling agent is a compound of polydimethylsiloxane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane, with a mass ratio of 1:9.
[0080] The raw materials for preparing the PVDC film layer are, by weight: 85 parts of vinylidene chloride monomer, 21 parts of modifier, 1.8 parts of emulsifier, 0.2 parts of initiator, and 52 parts of deionized water.
[0081] The mass percentage standard of the PVDC film layer is different from the mass percentage standard of the POE film layer.
[0082] The modifier is glycidyl acrylate.
[0083] The emulsifier is sodium lauryl sulfate.
[0084] The initiator is a compound of dimethyl azobisisobutyrate and potassium persulfate, with a mass ratio of 1:12.
[0085] The PVDC film preparation method comprises the following steps: after the materials are uniformly mixed, ethylenediaminetetraacetic acid is used to adjust the pH value of the emulsion to 6.5, the temperature is raised to 50° C. under N2 conditions, the mixture is stirred for 10 hours, and the mixture is cooled and discharged.
[0086] On the other hand, this embodiment 3 discloses a method for preparing the composite high-barrier membrane, which is obtained by co-extruding the three-layer mixed material, cooling and shaping.
[0087] Example 4
[0088] This embodiment 4 discloses a composite high-barrier film based on POE material, and the composite high-barrier film includes three layers, namely: a POE film layer, an EVOH film layer, and a POE film layer.
[0089] The raw materials for preparing the POE film layer are as follows, by weight: 77 parts of POE, 1.2 parts of toughening agent polylactic acid, 0.56 parts of peroxide crosslinking agent, and 0.34 parts of silane coupling agent.
[0090] The POE was purchased from SABIC of Korea with the brand number C0560D.
[0091] The toughening agent polylactic acid was purchased from Shanghai Tongjieliang Biomaterials Co., Ltd., model number IM9005.
[0092] The toughening agent polylactic acid was purchased from NatureWorks, USA, model number 2003D.
[0093] The peroxide crosslinking agent is tert-butyl peroxide 3,5,5-trimethylhexanoate.
[0094] The silane coupling agent is a compound of polydimethylsiloxane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane, with a mass ratio of 1:9.
[0095] The EVOH was purchased from Kuraray of Japan with the brand number F104B.
[0096] On the other hand, this embodiment 4 discloses a method for preparing the composite high-barrier membrane, which is obtained by co-extruding the three-layer mixed material, cooling and shaping.
[0097] Example 5
[0098] The difference between Example 5 and Example 3 is that the POE is purchased from Dow Chemical of the United States with a brand name of 8003 and a melt index of 1 g / 10 min (the melt index is measured at 190°C and 2.16 kg), and the toughening agent polylactic acid is purchased from NatureWorks of the United States with a model number of 2003D and a melt index of 5-7 g / 10 min (the melt index is measured at 210°C and 2.16 kg).
[0099] Example 6
[0100] The difference between Example 6 and Example 4 is that the POE is purchased from Dow Chemical of the United States with a brand name of 8003 and a melt index of 1 g / 10 min (the melt index is measured at 190°C and 2.16 kg), and the toughening agent polylactic acid is purchased from NatureWorks of the United States with a model number of 2003D and a melt index of 5-7 g / 10 min (the melt index is measured at 210°C and 2.16 kg).
[0101] Example 7
[0102] The difference between Example 7 and Example 3 is that the silane coupling agent is replaced by ethylene glycol dimethacrylate.
[0103] Example 8
[0104] The difference between Example 8 and Example 4 is that the silane coupling agent is replaced by ethylene glycol dimethacrylate.
[0105] Example 9
[0106] The difference between Example 9 and Example 3 is that the initiator is potassium persulfate.
[0107] Example 10
[0108] The difference between Example 10 and Example 4 is that the initiator is potassium persulfate.
[0109] Embodiment 11
[0110] The difference between Example 11 and Example 4 is that the EVOH is purchased from Japan Synthetic Chemical Co., Ltd. with a brand name of DC3203F and a melt index of 3.2 g / 10 min (the melt index is measured at 210° C. and 2.16 kg).
[0111] Performance Test:
[0112] Refer to the methods and standards of GB / T298482018 "Ethylene Vinyl Acetate Copolymer (EVA) Film for Photovoltaic Module Encapsulation" to measure and evaluate the basic performance of each group of films. Select the same batch and model of cells, use each group of films for encapsulation, and perform power attenuation test under the same conditions with reference to DINIEC / TS6280412017 method (temperature 85℃±2℃, humidity 85%±5%, test 1000h).
[0113]
[0114]
Claims
1. A composite high barrier film based on POE material, characterized in that: The composite high barrier film comprises three layers, which are: a POE film layer, a PVDC film layer or an EVOH film layer, and a POE film layer; The raw materials for preparing the POE film layer include: 60-85 parts of POE, 1-1.8 parts of toughening agent polylactic acid, 0.4-0.9 parts of peroxide crosslinking agent, and 0.15-0.58 parts of silane coupling agent; the POE melt index is less than 0.9 g / 10min, and the melt index is measured under the conditions of 190°C and 2.16kg; The melt index of the toughening agent polylactic acid is greater than 15g / 10min, and the melt index is measured at 210°C and 2.16kg; The silane coupling agent is a compound of polydimethylsiloxane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane, with a mass ratio of 1:(7-12); The raw materials for preparing the PVDC film layer are: 75-95 parts of vinylidene chloride monomer, 20-24 parts of modifier, 1-2 parts of emulsifier, 0.2-0.3 parts of initiator, and 50-60 parts of deionized water; the initiator is a compound of dimethyl azobisisobutyrate and potassium persulfate, with a mass ratio of 1: (8-15); The EVOH melt index is greater than 3.5 g / 10 min, and the melt index is measured under the conditions of 210° C. and 2.16 kg.
2. The composite high barrier film according to claim 1, characterized in that: The peroxide crosslinking agent is selected from one or more of tert-butyl perbenzoate (TBPB), tert-butyl peroxide 3,5,5-trimethylhexanoate (TBPIN), diisopropylbenzene peroxide (DCP), and 1,4-di-tert-butylperoxyisopropylbenzene.
3. A method for preparing a composite high barrier film according to any one of claims 1 to 2, characterized in that: The three-layer mixed material is co-extruded, cooled and formed.
4. An application of the composite high barrier film according to any one of claims 1 to 2, characterized in that: Applicable to N-type batteries and HJT batteries.
Citation Information
Patent Citations
High-volume resistivity EVA (Ethylene Vinyl-acetate Copolymer) rubber film and preparation process thereof
CN103146315A
Method for encapsulating an electronic arrangement
CN102576822A
PVDC emulsion and solar cell backboard therewith
CN110437363A
Packaging adhesive film for solar cell and preparation method thereof
CN113004815A
Heterojunction packaging integrated film of dual-protection copper gate and preparation method of heterojunction packaging integrated film
CN115449314A